Proceedings of the 21st IEEE Instrumentation and Measurement Technology Conference (IEEE Cat. No.04CH37510)
DOI: 10.1109/imtc.2004.1351228
|View full text |Cite
|
Sign up to set email alerts
|

A remotely controlled measurement system for education and training of experiments in wind tunnel

Abstract: In this paper an Integrated System to access the wind tunnel CTI (Calibration Tunnel number 1) sited at CIRA (Italian Aerospace Research Center), through a scalable networking infrastructure and supporting multimedia technology, is presented. The reliability and scalability of the porposed architecture, allows the execution of complex tests in a remote laboratory without the presnece of operators on site. The system represents an e-learning support where the instructor and the students, connected to a relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…Szükségessé vált a gyakorlatok megszervezése oly módon, hogy a hallgatók személyes jelenléte csökkenthető legyen. Ezt támogatják egyes távoktatási módszerek, mint például a mérőhelyek műszereinek távoli elérése, távvezérlése interneten keresztül [1], vagy a szimulációs szoftverek használata [2].…”
Section: Bevezetésunclassified
“…Szükségessé vált a gyakorlatok megszervezése oly módon, hogy a hallgatók személyes jelenléte csökkenthető legyen. Ezt támogatják egyes távoktatási módszerek, mint például a mérőhelyek műszereinek távoli elérése, távvezérlése interneten keresztül [1], vagy a szimulációs szoftverek használata [2].…”
Section: Bevezetésunclassified
“…A good review of developments in the systems engineering area can be found in [11]. The aim of remote laboratories could be to provide complementary learning tools but also to provide facilities to access to big or singular equipments [12] or even to fully implement the laboratory activities [13]. Two literature reviews can be found in [14] and [15].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the remote labs for engineering education are found in control [5], [6], [7] and electronics or circuit theory [8], [9], [10] areas. The aim of remote laboratories could be to provide complementary learning tools but also to give access to big equipments [12] or to fully implement the laboratory activities [13].…”
Section: Introductionmentioning
confidence: 99%